2008
DOI: 10.1021/es702304c
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Pharmaceuticals and Other Anthropogenic Waste Indicators in Earthworms from Agricultural Soil Amended With Biosolid or Swine Manure

Abstract: Analysis of earthworms offers potential for assessing the transfer of organic anthropogenic waste indicators (AWIs) derived from land-applied biosolid or manure to biota. Earthworms and soil samples were collected from three Midwest agricultural fields to measure the presence and potential for transfer of 77 AWIs from land-applied biosolids and livestock manure to earthworms. The sites consisted of a soybean field with no amendments of human or livestock waste (Site 1), a soybean field amended with biosolids f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
215
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(235 citation statements)
references
References 66 publications
(96 reference statements)
4
215
7
Order By: Relevance
“…Six compounds (clotrimazole, miconazole, climbazole, methylparaben, triclosan, and triclocarben) were found at levels of several ngg −1 in the sludge-amended soil samples. The concentrations of triclosan detected in this study were lower than those in a previous report of concentrations up to 160 ngg −1 [44]. Icaridin, a relatively new type of insect repellent, was not found in all the samples, probably because it has a limited use in China.…”
Section: Methods Validationcontrasting
confidence: 95%
“…Six compounds (clotrimazole, miconazole, climbazole, methylparaben, triclosan, and triclocarben) were found at levels of several ngg −1 in the sludge-amended soil samples. The concentrations of triclosan detected in this study were lower than those in a previous report of concentrations up to 160 ngg −1 [44]. Icaridin, a relatively new type of insect repellent, was not found in all the samples, probably because it has a limited use in China.…”
Section: Methods Validationcontrasting
confidence: 95%
“…The persistence of these three biocides may lead to accumulation in soils and organisms in the environment. Uptake of these biocides by plants and bioaccumulation in earthworms from soils applied with biosolids is possible as shown for some pharmaceutical and personal care products (Kinney et al, 2008;Wu et al, 2010). A proper risk assessment for terrestrial organisms is not possible at this stage because of the lack of relevant toxicological data.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the application of biosolids on agricultural land is still not allowed due to concerns with various contaminants in the biosolid (Daughton and Ternes, 1999;Gottschall et al, 2012;Kinney et al, 2008;Langdon et al, 2012;McClellan and Halden, 2010;Walters et al, 2010). Chinese Ministry of Agriculture initiated field trials of biosolids in 2006 to address the concerns associated with biosolid application on agricultural land.…”
Section: Introductionmentioning
confidence: 99%
“…Earthworms process large amounts of soil through their feeding and burrowing activities (Lavelle et al, 1997;Shan et al, 2010). Consequently, earthworms can accumulate many organic and inorganic soil pollutants, and they are therefore ideal testing organisms for the bioaccumulation of pollutants in soil (Jager et al, 2003;Kinney et al, 2008). Many studies have reported the bioaccumulation of various contaminants in earthworms, including heavy metals and organic pollutants (Kizilkaya, 2004;Jager et al, 2005;Shang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%